Strengthening The Synergy of Iman, Islam, and Ihsan Through Tadabbur of Qur’anic Messages - Achmad, Achmad (International Tatho Academics, 2025)
This research aims to identify the construction of religiosity values ​​contained in the Al-Quran through the tadabbur approach. Using a qualitative approach, the research process began with a literature study to collect and examine various sources that discuss the concept of tadabbur. Next, relevant verses of the Qur'an are selected and analyzed in depth, including understanding the literal, contextual meaning and implications. The results of this research underline the importance of reflection and contextual understanding of Islamic teachings, which can improve the spiritual quality of individuals and society. By contemplating the meaning of the verses of the Qur'an, individuals are expected to be able to internalize these teachings in everyday life. It is hoped that this research can make a significant contribution to the development of knowledge in the study of the Qur’an and spiritual practices among Muslims, as well as encouraging people to be more active in carrying out tadabbur.